Adoption of parcel locker in Malaysia: Literature review and research agenda - Fara Adura, Mohd Yusoff; Fazeeda, Mohamad; Puteri Fadzline, Muhamad Tamyez; Siti Aisyah, Panatik (GBMR, 2023)
Purpose: This paper intends to establish conceptual frameworks and propose groundwork for empirical research in identifying factors that influence consumers' intention and adoption of parcel lockers. A conceptual framework was developed based on the Unified Theory of Acceptance and Use of Technology (UTAUT) construct, i.e., effort expectancy, performance expectancy, social influence, and facilitating condition. In addition, this study also seeks to propose the role of resistance to change in moderating the relationship between intention and adoption of parcel locker. Methodology: The methodology used in this article is a literature review and conceptualisation of how UTAUT constructs could influence the intention and adoption of Malaysian consumers on the use of parcel lockers as last-mile delivery services. Thus, this paper used a conceptual approach that reviewed the article from journals, conference papers, and theses. Dimensions and measurements of the variables in this investigation were derived from previous studies and suggestions. Findings: The expected findings of this study were to determine the most important factors contributing to the intention and adoption of parcel lockers among Malaysian consumers. Therefore, the relevant companies and government agencies can improve services and meet the needs and preferences of consumers to utilise parcel lockers, thereby expanding parcel locker usage in the future. Research limitations/implications: The quantitative technique will be employed for this study, limiting researchers' ability to investigate beyond the factors that will be investigated. Practical implications: The findings are expected to be useful to several parties, including courier companies, the government, and online sellers, in terms of future planning to increase the intention and adoption of parcel lockers in Malaysia. Originality/value: This study proposed a conceptual framework for the factors affecting the intention and adoption of parcel lockers service, specifically in the Malaysian context.